Restorative justice in Islamic criminal legal system - Wan Muhammad, Ramizah (2016)
This paper discusses the concept of restorative justice in Islamic criminal law leased upon the Shari’ah. Many people have discussed about the punishments provided in the Qur’anic text and traditions of the Prophet S.A.W which is under the retributive justice and failed to highlight the existence of restorative justice in which shari’ah emphasized upon too. The concept of forgiveness is one of issues to be discussed under the homicide and bodily injuries cases, where the power to forgive is given to the family of the victim or to the victim himself in forgiving the offender who have caused the injuries to the victim. Justice in Islam is associated with taq’wa or piety to Allah. Sometimes by forgiving the offender and giving him second chance is one step closer to taq’wa. The purpose of punishment is not only to punish the offender particularly but rather to restore peace in the community, physically and spiritually. The implementation of Islamic criminal law is to protect the individual living in a country and to encourage every person in the country to help each other to becomea better person. This paper is to look into the above aspects and highlight the possibilities to realize the concept in our legal system.